Medical Record Summary for Computer Operation - Gordon, B. L. (Methods of Information in Medicine, 1977)
Key items of the source medical record are valuable in computing, notably when presented in a wellordered summary. These designations are preferred to complete coverage and narration. The computer file includes patient identification, reasons for the consultation, findings, treatment, outcome and successive episodes and/or observations; academic diagnoses are desirable if/when proved. Descriptors or nouns and qualifiers or adjectives constitute the computer vocabulary for key items, e.g., paincliest-precordium-sudden-severe-radiation-chin, ECG inverted T wave. Random numbers are useful to attain maximum simplicity and specificity of the input for filing, handling, timely communication and subsequent classification.
Keywords: Medical Record Processing; Current Medical Information and Terminology (CMIT); Simplified Medical Records System (SMRS)